Sustainable clothing: perspectives from US and Chinese young Millennials. Issue 11 (11th November 2019) - Su, Jin; Watchravesringkan, Kittichai (Tu); Zhou, Jianheng; Gil, Maria
Abstract : Purpose: The purpose of this paper is to understand US and Chinese young Millennials' perceptions of and consumption behaviour towards sustainable apparel products. Design/methodology/approach: Quantitative research was conducted, and empirical data were collected from 590 US college students and 379 Chinese college students. Findings: For both US and Chinese young Millennials, this study provides consistent empirical results of the positive and significant effects of young Millennials' apparel sustainability knowledge and personal values on consumer attitude towards sustainable clothing, which in turn positively and strongly impacts purchase intention. In addition, a cross-cultural comparative analysis reveals similarities and differences regarding apparel sustainability knowledge and values between young Millennial consumers in the US and China. Originality/value: The scale of environmental and social impacts from global apparel production and consumption makes sustainability increasingly important in the contemporary business environment. Young Millennials in the US and China represent large and influential consumer segments for sustainable consumption. This study contributes to the literature by surveying young Millennials in the US (developed market) and China (emerging market) in a cross-cultural context. The study offers insights into the global apparel industry in developing strategies for expanding sustainable apparel markets in the US and China.